Playing Approach to Passing Skills in Learning Futsal Sports - Agus Santosa; Syamsudar, Bangbang; Irfan, Muhamad (STKIP Paasundan Press, 2024)
This study aims to determine how much influence the playing approach has on passing skills in learning futsal sports. This study uses an experimental method using The one Group Pretest Posttest Design design. The population in this study were XII IPS 4 Man 3 Cirebon class students totaling 30 students, the sampling technique used was total sampling so the sample used in the study amounted to 30 students. The research instrument used was the Passing Test. Data analysis was carried out using Microsoft Excel and SPSS. Based on the results of research calculations and data analysis of the passing test results, the approach of playing in learning given in the form or situation of the game A significant increase can also be seen from the average which was originally 14.3 or 48% to 17.6 or 59% declared very good. So the conclusion in this study is: there is a significant influence of the playing approach on passing skills in learning futsal sports.